Primary Lactase Deficiency among Malnourished Children with Persistent Diarrhea in Tbilisi, Georgia - Nemsadze, Ketevan; Liluashvili, Eka; Kikodze, N.; Bakhtadze, T. (Journal of Child Science, 2017)
Persistent diarrhea became the major cause for diarrheal mortality in children from developing countries. This study was therefore designed to establish the prevalence of primary lactase deficiency and associated factors among mild malnourished children with persistent diarrhea. This was a prospective cohort study. The study population consisted of mild malnourished children with persistent diarrhea aged 3–24 months admitted between October 2014 and September 2015. The Gomez classification of malnutrition was used. A mild malnourished child was whose weight-for-height was less than 75%–90% of the median National Centre for Health Statistics (NCHS)/WHO reference median. The study included 78 malnourished children with persistent diarrhea 3–24 months of age. The prevalence of primary lactase deficiency among the study children was 41.0%. The reasons of persistent diarrhea in lactose tolerant group were: Rotavirus infection – 33.3%, Bacterial gastroenteritis –20.5% (Enteropathogenic E.coli (EPEC) – 7.7%, Shigella – 6.4%, Yersinia enterocolitica – 3.8%, Salmonella – 2.6 %) and Gastroenteritis of unknown etiology – 5.1%. Only 4 children had Rotavirus infection in lactose intolerant group. The relationship between diarrhea and malnutrition is bidirectional: diarrhea leads to malnutrition while malnutrition aggravates the course of diarrhea. Lactose intolerance is a relatively common cause of persistent diarrhea. The most common cause of primary lactase deficiency is lactase enzyme non-persistence.
Keywords: primary lactase deficiency; persistent diarrhea